Reciprocal Symmetry and its Relation to Einstein’s Postulate, Lorentz Transformation and Discreteness - Ahmad, Mushfiq (Journal of Scientific Research, 2009)
Objectivity demands that kinematics should be independent of the quantities (velocities or their reciprocals) we define. This demand is translated as Reciprocal Symmetry (RS), which we have defined. We have shown that RS gives an upper bound velocity, the mathematical analogue of Einstein's postulate, and Lorentz transformation. RS also requires discreteness. RS promises to bridge the gap between relativity and quantum mechanics. Keywords: Galilean velocity; Lorentz-algebraic velocity; Reciprocal symmetry; Reciprocal velocity; Reciprocal symmetric distance; Discrete time; Discreteness. © 2009 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. DOI: 10.3329/jsr.v1i2.1875